Polyfunctionality and cultural value of public space: historical and cultural study of an urban square - I. I. Maslikova (Ukrainian Cultural Studies, 2019)
The article explores changes in the organization and functioning of public space in cities in the context of sociocultural dynamics – from antiquity to modernity. The sociocultural features of open urban space in ancient Greece and Rome, Renaissance Italy, modern Europe, the USA, Latin America, Ukraine are clarified. The experience of the functioning and management of public space is analyzed on specific examples of world- famous urban squares – Antique agora, roman forum, piazza del Campo in Siena, piazza della Signoria in Florence, piazza San Marco in Venice, Union Square in New York, Latin American squares, Bibikovsky boulevard and University park in old Kyiv, "Maydan" – Independence Square in contemporary Kyiv. Particular attention is being given to transformations of ceremonial, religious, recreational, economic, political, aesthetic and moral functions of open public space. Urban squares are places for official celebrations and religious rituals. They serves as a place of a rest, realization of creative ideas and are a conductor of public communication. Public spaces create opportunities for trade, affect the formation and retention of real estate prices, and are a means of attracting investment and business development in them and adjacent territories. All these provide opportunities for uniting citizens for joint projects and activities, political protests or symbolization of power. It is noted that the cultural value of the modern square is manifested in architectural forms, aesthetics of recreational areas and historical monuments, and is associated with its ability to be a place for the proclamation and implementation of high moral ideals of order, equality, solidarity, freedom, independence, human dignity, the value of moral rights and civic virtues. From the time of antiquity to the present day, the central squares of cities, as a public space, reproduce the aesthetics of the city and become a symbol of spiritual and political power, since temples, municipalities, financial and commercial institutions, theaters, and restaurants are often concentrated in such spaces.